A novel multi-criteria decision making approach for selection of reverse manufacturing alternative. (1st January 2013) - Mahapatara, Siba Sankar; Sharma, S.K.; Parappagoudar, M.B.
Nowadays, reverse logistics (RL) has received considerable attention due to its huge potential of product recovery from unused/end-of-life products for the purpose of capturing value. The selection of favourable product recovery option for the product arriving at workplace has become a key issue for effective implementation of RL. Many decision making methods have been developed to deal with such a multiple criteria decision making problem. Keeping in view of RL implementation, a method is proposed in this paper for designing effective policy for reverse manufacturing alternative selection. The proposed method attempts to consider both subjective and objective weights of qualitative and quantitative attributes and integrates them to decide the importance of weights of the alternatives. Furthermore, fuzzy rating values assigned by the decision makers are converted into crisp values to simplify the calculations. This paper presents a group decision making tool combining RL with a novel multiple criterion decision making approach to decide reverse manufacturing alternatives.